"Structure from Motion" Low-cost alternative for the registration of built heritage - Sánchez Carrión, Nadia (2015)
The following article is of applicative and instrumental character and was drawn from the results of a series of architectural projects in which the intervention of buildings considered heritage gave opportunity to look beyond traditional methods and processes for graphical documentation . A methodology was developed that involves using the Visual System software Structure from Motion, from which a three-dimensional model is obtained; through a combination of imaging techniques the graphic documentation and survey of pathological lesions of the building is improved. Two resources were optimized to achieve the viability of the projects: time and budget, both scarce. This led to the proposal of a strategy based on methods that allow optimal performance in the process of graphic documentation, ensuring fidelity in the current representation of the building, and it’s injuries and pathologies.